Labor supply as a discrete choice among latent jobs - John K. Dagsvik; Zhiyang Jia (Statistics Norway, Research Department, 2012)
This paper discusses a modeling framework in which workers are assumed to choose their preferred job from latent worker-specific choice sets. This point of departure yields a framework that formalizes the widely used ad hoc approaches (fixed cost of working and dummies at peak hours) in the literature of discrete labor supply models. We discuss the conditions under which the preferences and job opportunity restrictions can be separated using conventional data on hours and wages only. Subsequently, we show that the framework is consistent with stochastic choice sets and a relaxation of the IIA assumption. An empirical model version for married/cohabiting couples is estimated using Norwegian micro data. Based on the empirical model, we discuss further important empirical issues, such as functional form, prediction performance and simulation of counterfactual policy reforms.
Keywords: J22; C51; 330; Labor supply; non-pecuniary job attributes; latent choice sets; random utility models.